Cost Comparison Between 2 Responses to Hepatitis A Virus Incidents in Restaurant Food Handlers—New York City, 2015 and 2017. Issue 2 (March 2020) - Baum, Sarah E.; Reddy, Vasudha; Vora, Neil M.; Balter, Sharon; Daskalakis, Demetre; Barbot, Oxiris; Misener, Mark; Rakeman, Jennifer; Rojas, John; Starr, David; Waechter, HaeNa; Zucker, Jane; et al.
Abstract : Context: While the New York City Department of Health and Mental Hygiene (DOHMH) can use agency-wide emergency activation to respond to a hepatitis A virus–infected food handler, there is a need to identify alternative responses that conserve scarce resources. Objective: To compare the costs incurred by DOHMH of responding to a hepatitis A case in restaurant food handlers using an agency-wide emergency activation (2015) versus the cost of collaborating with a private network of urgent care clinics (2017). Design: We partially evaluate the costs incurred by DOHMH of responding to a hepatitis A case in a restaurant food handler using agency-wide emergency activation (2015) with the cost of collaborating with a private network of urgent care clinics (2017) estimated for a scenario in which DOHMH incurred the retail cost of services rendered. Results: Costs incurred by DOHMH for emergency activation were $65 831 ($238 per restaurant employee evaluated) of which DOHMH personnel services accounted for 85% ($55 854). Costs of collaboration would have totaled $50 914 ($253 per restaurant employee evaluated) of which personnel services accounted for 6% ($3146). Conclusions: Accounting for incident size, collaborating with the clinic network was more expensive than agency-wide emergency activation, though required fewer DOHMH personnel services.